The role of state information policy in shaping democratic transformation amid hybrid threats - Balan, Sergii; Vorotynskyy, Vadym; Patalakha, Valerii; Rybak, Iryna; Tarasiuk, Volodymyr; Рибак, Ірина Вікторівна; Рибак, Ірина (Universidade Federal do Paraná, 2025)
Introduction: Hybrid threats, including disinformation, propaganda, and cyberattacks, pose significant challenges to democratic processes. This study examines how information policies can help safeguard democracy, focusing on the Ukrainian case after 2014, when such threats intensified as tools for institutional destabilization and erosion of public trust. Materials and methods: The study takes a multidisciplinary approach, integrating document analysis, literature review, public policy evaluation, and case studies, drawing on sources such as international reports, national legislation, fact-checking platforms, and records of informational attacks. Empirical examples include the spread of false information during Brexit, fabricated narratives about the conflict in eastern Ukraine, and global cybersecurity incidents such as WannaCry and NotPetya. Results: Our findings show that hybrid threats erode political participation, deepen polarization, and weaken democratic institutions. The study identifies three main axes of response: strengthening Ukraine's legal framework on media and communication, promoting interinstitutional coordination for monitoring and rapid response, and leveraging both state and independent platforms to identify and counter manipulative content. The research also demonstrates that media literacy and government transparency play a critical role in building societal resilience against disinformation campaigns. Discussion: The analysis indicates that balanced information policies are vital for mitigating external interference while preventing excessive state measures that could threaten civil liberties. The Ukrainian case underscores the importance of adaptive strategies, international cooperation, and the integration of advanced technologies to safeguard the democratic public sphere under conditions of instability. Information policy therefore emerges as a strategic instrument for safeguarding democratic stability, with its effectiveness resting on robust institutions, continuous monitoring, and rapid responsiveness in the contemporary information environment.
Keywords: digital governance; public sphere; civic engagement; cybersecurity; information platforms